Seroprevalence and associated risk factors for bovine leptospirosis in Egypt - Selim, Abdelfattah; Marzok, Mohamed; Gattan, Hattan S.; Abdelhady, Abdelhamed; Salem, Mohamed; Hereba, Abdelrahman M. (Scientific reports, 2024)
Leptospirosis is caused by pathogenic bacteria of the genus Leptospira and is one of causative agents of reproductive problems leading to negative economic impact on bovine worldwide. The goal of this study was to investigate the seroprevalence of Leptospira spp. in cattle in some governorates of Egypt's Nile Delta and assess the risk factors for infection. A total of 410 serum samples were collected from cattle and examined using microscopic agglutination test. The overall seroprevalence was 10.2% and the most prevalent serovars were Icterohaemorrhagiae, Pomona and Canicola. In addition, the potential risk factors were associated Leptospira spp. infection were age, herd size, history of abortion, presence of dogs and rodent control. Thus, leptospirosis is common in dairy cattle in the Nile Delta and  the presence of rodents in feed and dog-accessible pastures increases the risk of Leptospira spp. infection among animals.